Life And Work of Abu Mansur AlMoturidi and Theology (Eurasian Scientific Herald, 2022)
Abu Mansur al-Moturidi's contribution to the development of theology in Mawarounnahr is incomparable. The doctrine he founded later spread beyond the Samarkand school of kalam and spread throughout the Islamic world, becoming known as one of the two largest schools of Sunni Islam (along with Ashariya).